IMPROVING CHILDREN'S VISUAL SPATIAL INTELLIGENCE THROUGH DRAWING AT BALI STREET MUMS AND KIDS PROJECT FOUNDATION, DENPASAR - Sumadewi, Komang Trisna; Yupardhi, Toddy Hendrawan; Primatanti, Putu Asih; Harkitasari, Saktivi (Universitas Nahdlatul Ulama Surabaya, 2024)
Presently, multiple educational options exist for both primary school and higher education. The entire education system is designed to assist students in cultivating a range of abilities or intelligences inherent in each individual, encompassing mental and physical aspects. This concept is usually referred to as